Problems and Prospects of ICT Use in Higher Education: A Focus on Geography Education - Adhikari, Sapana; Shrestha, Suman Kumar; Khadka, Arjunbikram; Joshi, Jnanee (Journal of Research and Development, 2026)
Using Information and Communication Technology (ICT) in education has tremendous potential to transform teaching and learning. It has more potential in the spatially based subject like geography that depends on spatial information, electronic mapping, and human–environment investigation. The aim of this article was to assess prospects and problems of use of ICT in higher education in general and geography in particular. This research employed a qualitative method with a descriptive research design, utilizing both primary and secondary sources of information. , the study interviewed students, ICT teachers, informants, and campus managers in urban and semi-urban campuses and asked them questions on problems and prospects. ICT tools such as Geographic Information Systems (GIS), remote sensing, virtual simulation, and digital cartography enable interactive learning, virtual fieldwork, and collaborative investigation, resulting in spatial literacy and skill application. Integration of ICT in Nepal is led by ICT in Education Master Plan and Digital Nepal Framework; implementation is slowed down by infrastructural constraints, low digital literacy levels, teachers' training requirements, and budgetary constraints, especially at rural sites. The COVID-19 pandemic has paved the prospects of distance learning while highlighting persistent access and readiness inequities. Evidence shows that students in Nepal recognize the importance of ICT for their future work and actively seek knowledge despite infrastructural and pedagogical constraints; by strategically addressing gaps in infrastructure, local digital content, teacher training, inclusive curricula, and equitable access, ICT can be deeply embedded into higher education, revolutionizing the teaching of geography, stimulating interest in learning, and reducing disparities across the system.